Eight Steps to Plan Strategically in Micro-Enterprises Run by “Non-Management“ - Acevedo Tabares, Alejandro
This article presents an analysis of the importance of strategic planning as key success factor of the company, beginning with an interpretation of the article A look at the historical development of organizational strategy (Castellanos & Cruz Narciso Pulido, 2014) where it identifies and describes the different tools that over time have been proposed thinkers such as Porter, Ansoff, Senge and others, then propose, based on these authors, its own model of planning and strategic foresight, whose order to provide managers “not managers” of micro efficient methodology for strategic planning based on eight easy steps and simple to implement but crucial to chart the course and align all efforts of the company towards a desired future elements. (Define the mission of the company, define the vision of the company, conduct a situational analysis, structure the SWOT matrix, define the key variables, plan scenarios, design a plan of action, set up a monitoring and control mechanism).